Розробка рекомендаційних функцій системи електронної комерції центру коворкінгу - Сиротенко, О. Г. (ХНУРЕ, 2024)
The report describes the stages of design and development of the e-commerce system of the coworking centre with the implementation of the business function of preparing personal recommendations based on user needs using Content-Based and Knowledge-Based determining recommendations methods. The object of recommendations is the rooms of the coworking centre where physical workplaces are rented. Preparation of personal recommendations is carried out both based on users' requirements to the room characteristics and based on their history of renting workplaces.
Keywords: рекомендаційні функції; електронна комерція; центр коворкінгу; система рекомендацій